Embracing the Big Data Analytics Capabilities on Firm’s Performance in the Digital Transformation Era of Family-Owned Businesses: A Study of the Fashion Industry of Pakistan (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
In today’s times, the advancements in the technological world have been growing day by day since the upcoming of the several breakthrough innovations such as innovative tosols and techniques which helps businesses to upgrade their practices with help of artificial intelligence, big data analytics, cloud computing and business intelligence which has been shifting the business paradigms (Zeng & Khan, 2018; Sheng et al., 2019). However, big data analytics is also playing a huge role in these times as it is found as a true game changer in today’s businesses which increases the strategic as well as operation performances of the firm by uplifting the efficiency in the firm decision making (Wamba, Gunasekaran, Akter, Ren, Fan, Dubey & Childe, 2017). Moreover, researchers claim that big data analytics can be a major indicator and driver of strategic innovation in the firm which results as a high profitability in the firm’s performance. (Zhang & Yuan, 2023).Moreover, big data analytics supports the instincts of the management and creativity through the prompt and continuous availability of real-time information (Cheah, 2017). Moreover, researchers claim that big data analytics can be a major indicator and driver of strategic innovation in the firm which results as a high profitability in the firm’s performance. (Zhang & Yuan, 2023). Additionally, innovation takes place based on the data-driven models for decision making allows organizations to develop and design innovative products and services which may address the consumer needs as well as minimize the innovation-based risk (Ji, Yu, Tan, Kumar & Gupta., 2024).In this study the data was collected through family-owned business managers. The sample size of the study was 236 managers from textile industry of family-owned business via using purposive sampling technique. This study was built on quantitate approach where data was collected via surveys. For the analysis purpose the data was analyzed via PLS-SEM for quantitative data Furthermore, the findings of this research study indicates that big data analytics capabilities have a positive effect on the strategic innovation of the firm which increases the firm’s performance such as market performance as well as financial performance of an organization. Technological transformation plays an important role as it enhance the business practices in economy where the transitions of business can positively impact in a developing county such as Pakistan.